The Integration of Certain Products of Special Functions (Global Journal of Science Frontier Research, 2013)
The aim of the present paper is to obtain a finite integral involving a product of Fujiwara’s polynomial [7], M-series [15], a general class of polynomial [10], with the H-function of several complex variables [11]. The results are quite general in nature hence encompass many new, known and unknown results hitherto in the literature.
Keywords: unknown results hitherto literature